The Integration Of The Traditional Leadership Into The Structure Of Local Government In Yobe State Nigeria Hamza Suleiman Danladi - Danladi, Hamza Suleiman (2023)
The issue of integration of traditional leadership in government at local level has led to the emergence of debates on two issues. The first, relates to the relevance of traditional leadership to contemporary democratic concerns; second, it relates to the dilemma on whether traditional institutions are resources or barriers to progress and modernization. This study examined the integration of traditional leadership into the structure of local government in Yobe State Nigeria. The study used Neo-traditionalism and State-Traditional Interaction theories as theoretical lens. The study was qualitative in nature and in-depth interviews were administered on 16 participants that comprised the traditional leaders, government officials, non-governmental organization officials, association leaders, and experts who were purposively selected across three local governments in the state. While the secondary data involves journal articles, government official reports, news papers and magzines, and theses. In terms of data analysis, Braun and Clarke six steps of thematic analysis was employed. The findings explores strategies with which traditional leaders could be integrated in the local government structure in such a way that it will not conflict with the authority and duties of the elected officials of the local government as opposed to the Neo-modernist view. The findings also show that traditional leaders constitute resources with which they enormously contribute to the development of local government in Yobe State. The findings further reveal that there is good and working relationship between the traditional leaders and the local government officials.